Inflammation and echocardiographic parameters of ventricular hypertrophy in a cohort with preserved cardiac function - Medenwald, D (BMJ Publishing Group, 2014)
OBJECTIVE: To investigate the association between inflammation and selective echocardiographic parameters (EP) characteristic for ventricular hypertrophy in cross-sectional and longitudinal population-based analyses. METHODS: Baseline (711 men, 659 women: 45–83 years) and 4-year follow-up data (622 men, 540 women) of the prospective, population-based CARdio-vascular disease, Living and Ageing in Halle (CARLA)study after exclusion of participants with cardiacvascular diseases were analysed. Inflammation parameters: soluble tumour necrosis factor receptor 1 (sTNF-R1), high-sensitivity C reactive protein (hsCRP) and interleukin 6 (IL-6). EPs: left ventricular mass (LVM), left atrial systolic dimension (LADS), interventricular septum diameter (IVSD), posterior wall dimension (PWD), left ventricular diastolic diameter (LVDD), ejection fraction according to Teichholz (EF). For the longitudinal analyses baseline to follow-up differences were considered. Effect sizes were determined by using multiple linear regression and mixed models. Missing values were replaced by means of multiple imputations. RESULTS: Men had higher sTNF-R1 levels; means of hsCRP and IL-6 were similar in men and women. In multiple regression models, sTNF-R1 was associated with LADS (1.4 mm/1000 pg/mL sTNF-R1, 95% CI 0.6 to 2.1) in men. Respecting confounder hsCRP was associated with LVM (5.2 g/10 mg/L hsCRP, 95% CI 1.6 to 8.8), IVSD (0.2 mm/10 mg/L hsCRP, 95% CI 0 to 0.3) and PWD (0.2 mm/10 mg/L hsCRP, 95% CI 0.1 to 0.3) in women, while there were no relevant effects in analysis of IL-6 in both sexes. The baseline to follow-up change in EPs was not relevantly associated with sTNF-R1, hsCRP or IL-6. CONCLUSIONS: STNF-R1, hsCRP and IL-6 were inadequate predictors for structural changes of the heart at follow-up, while weak cross-sectional associations are restricted to certain EPs and depend on sex.